1 - Editorial - Journal System, (African Sociological Review, 2023)
This issue is one of two that spotlight Francophone West Africa, a long-planned project. Here, all the papers are in French, an editorial decision informed by the need to increase further the visibility and readership of the journal in French speaking countries worldwide. To be sure, this has been the case in the past decades as revealed in our analysis of downloads of papers in French following increased submission and published peer review of such papers. Yet, as the journal became swamped with submissions in French, we feel we must not relent in ensuring that they do not lag behind those in English. The second of the two issues will be in English with, of course, all papers focusing on Francophone West Africa. It will focus on different socio-economic aspects of some of the countries the authors chose for their respective research and analyses. Dr Hélène V Quashie, of LARTES-IFAN Université Cheikh Anta Diop / Institut des Mondes Africains Senegal was charged with the responsibility of co-ordinating all the papers for this special issue, in terms of getting them ready after the mandatory blind review. She titled the issue which is essentially a monograph given its specialised focus.